PEMBATASAN HAK PILIH TENTARA NASIONAL INDONESIA DAN KEPOLISIAN NEGARA REPUBLIK INDONESIA DALAM PEMILIHAN UMUM DI INDONESIA - Alfianim '; Dodi Haryono; Abdul Ghafur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
In this reformation era, there were discourses on the recovery of the right to vote for members of the Indonesian National Army (TNI) and Indonesian National Police (Polri) in the General Election. The desire of the recovery based on the development process of democratization that puts the right to vote as a fundamental right that can't be criss / violated by the State. The purpose of this essay, that is ; First, How is the restrictions adjustment on suffrage to select the Armed Forces of Indonesia and the Indonesian National Police in the General Election in Indonesia. second, whether the setting restrictions on the right to select the Armed Forces of Indonesia and the Indonesian National Police in Law Number 42 Year 2008 on General Election of President and Vice President of the draft Law Number 8 Year 2012 on General Election of members of the House of Representatives, Regional Representatives Council, and Regional House of Representatives in accordance with the Constitution of the Republic of Indonesia Year 1945, Third, How does the ideal setting suffrage Indonesian Armed Forces and the State Police Republic of Indonesia in the General Election in Indonesia. This type of research is a can be classified in this type of study Law Normative Law research, law research literature by researching legal principles. From the research results there are three main issues that can be inferred. First, the power settings on three periods of decline. In the Orde Lama, the armed forces and the police were given the right to vote in the election. In the Orde Baru, the Armed Forces are not given the right to choose, but the presence of the ABRI in the political sphere are specifically regulated through the mechanism of appointment in legislative institution. Whereas in the Reform Era, the right to vote and to vote for members of the military and police removed so that the military and police only carry out the task of the State without political rights inherent in the institution. Second, setting restrictions on the military and police suffrage in the election correspond with the Constitution of the Republic of Indonesia Year 1945. But the problem is the development of a democratic society in Indonesia has led to political consolidation in terms of providing same privilege for every citizen. Third, ideally right to choose the military and police in the election is a recognition of the right to vote the military and police as part of the protection of the human rights, strengthen democracy through voting rights of TNI and Polri, changes in regulations related to the protection of the right to choose the military and police.Keywords :Suffrage-TNI and POLRI-General Election